Analysis of the properties of alkaline-treated rape straw and stalk polyvinyl chloride composites. Issue 21 (November 2022) - Bichi, Abdulmalik Hamza; Zhang, Keping; Yang, Junqian; Chen, Dongsheng
Wood-plastic composites are being widely used more and more, and the bonding strength between fillers and matrix is an important factor affecting the properties of wood-plastic composites. In this study, rapeseed straw and rapeseed stalk were pretreated with sodium hydroxide and then filled with polyvinyl chloride matrix to prepare composites. The chemical composition, thermal stability, microstructure, physical properties, mechanical properties, and abrasive wear resistance of the composites were characterized, and the effects of different concentrations of alkaline treatment on rapeseed straw composite and rapeseed stalk composite were revealed. The results show that alkaline treatment has no significant effect on the chemical composition of the composites but has an obvious effect on other properties. Among them, after 1% alkaline treatment, rapeseed straw composite has the highest hardness, thermal stability, and impact strength, rapeseed stalk composite has the highest impact strength and bending strength. After 3% alkaline treatment, rapeseed straw composite has more wear resistance, rapeseed stalk composite has the highest density, the highest tensile strength, and more wear resistance. The rapeseed straw composite with 5% alkaline treatment has the highest density, and the rapeseed stalk composite with 7% alkaline treatment has the highest thermal stability. The hardness of rapeseed stalk composite and the tensile strength and bending strength of rapeseed straw composite decreased with the increase of alkaline treatment concentration.